Implementasi Analytical Hierarchy Process (AHP) dalam Pemilihan Supplier Chemical di PT Adis Dimension Footwear - Septiyana, Diah; Ari, Muhammad Afandi (Journal Industrial Manufacturing, 2022)
Supplier selection is one of the most important things in the company's purchasing activities. The selection of suppliers must be done carefully; if done wrong, it can cause disruption to the company's operations. Supplier selection becomes a multi-criteria problem, which includes qualitative and quantitative factors. One method that can be used for supplier selection is the AHP (Analytical Hierarchy Process) method. This research was conducted at a footwear industrial company, PT. Adis Dimension Footwear. The problems found in this research are: Which chemical supplier will be chosen by PT Adis Dimension Footwear based on the AHP method? Then what is the order of priority criteria and sub-criteria in the selection of chemical suppliers at PT. Adis Dimension Footwear? The sample for this research is the decision-makers and the parties who are in the purchasing and warehouse departments and know the performance of suppliers. This study uses the AHP (Analytical Hierarchy Process) method. From the results of the research, the importance of the criteria in supplier selection produces the following weights: The first order is quality criteria with a weighted value of 0.6333. Furthermore, the second rank is the criteria for delivery time with a weight of 0.2605, and the third is the price criteria with a weight of 0.1062. The chemical supplier selected based on research using the AHP method is Grand Chemical, which has a total weight of 0.4285. Asia Chemical Supplier comes in second with a total weight of 0.4093. Binzhou Longfeng Chemical Supplier comes in third place with an overall score. Keywords: Supplier selection, Analytical Hierarchy Process (AHP), footwear industrial, chemical supplier.